INTEGRAL/IBIS polarization detection in the hard and soft intermediate states of Swift J1727.8-1613 - Bouchet, T.; Rodriguez, J.; Cangemi, F.; Thalhammer, Philipp; Laurent, P.; Grinberg, V.; Wilms, Jörn; Pottschmidt, K. (Astronomy & Astrophysics, 2024)
Aims. Soft γ-ray emission (100 keV - 10 MeV) has previously been detected in the hard state of several microquasars. In some sources, this emission was found to be highly polarized and was suggested to be emitted at the base of the jet. Until now, no γ-ray polarization had been found in any other state. Methods. Using INTEGRAL/IBIS, we studied the soft γ-ray spectral and polarization properties of Swift J1727.8-1613 throughout its outburst. Results. We detect a highly polarized spectral component in both the hard intermediate state and the early stages of the soft intermediate state above 210 keV. In the hard intermediate state, the polarization angle significantly deviates from the compact jet angle projected onto the sky, whereas in the soft intermediate they are closely aligned. This constitutes the first detection of jet-aligned polarization in the soft γ-ray for a microquasar. We attribute this polarized spectral component to synchrotron emission from the jet, which indicates that some of the jet might persist into the softer states.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Gamma rays: general; Polarization; Stars: individual: Swift J1727.8-1613; X-rays: binaries